Assessment of shallow groundwater pollution by poultry waste in Minna, Nigeria - Aderemi, Adeoye Peter (2014)
A study to estimate the quantity of wastes generated from within some poultry farms in Minna, Niger State, Nigeria was conducted. Similarly, an assessment of management and disposal methods in order to develop sustainable manure management and pollution prevention plan for the purpose of accurate accounting of generation and manure composition was carried out. Effects of poultry waste dump on groundwater in the farms were also assessed using physicochemical and microbiological parameters. Structured questionnaires focusing on farm information, birds’ information and waste management were administered to the farm operators and their staffs in the farms. Fresh poultry manure samples were collected from layer, broiler and cockerel sections of three of the selected farms at bird’s growth stage of 6 and 12 weeks respectively. The samples were analyzed for nitrates, phosphates, heavy metals and bacteriological parameters. Findings from the questionnaires showed that a total of 2,131,400 layers, 1,224,840 broilers and 848,570 cockerels which amount to a total of 4,204,810 birds are raised annually in confinement in the farms covering an area of 170 hectares of land. The farms generate 100.97 metric tons of dead birds over a brooding cycle with about 26,565 metric ton of waste excluding slaughter house litter and hatchery wastes. Laboratory analysis results showed that the waste samples contained values as high as 206.75 mg/g and 34.21 mg/g of nitrates and phosphates respectively. Bacteriological values recorded are 25767.21 cfu/100mg, 48214 cfu/100mg and 17647.9 mg/g for faecal coliform, total coliform and faecal streptococci respectively. Arsenic concentration in the manure was found to be 37.3mg/g, chromium, 46.2 mg/g, copper, 121 mg/g, zinc, 396.2 mg/g and manganese concentration of 466.3 mg/g. The high heavy metals concentration was suspected to have originated from the addition of some antibiotics to poultry feeds for improved performance as shown in the feed composition. Management of the waste is poor in the farms visited as indiscriminate dumping on land and burning are major waste management systems in these farms. From the assessment, 52 % of the farmers do not treat the waste before dumping on land, 30 % add Aluminium sulphate while 9 % add ferric chloride. With respect to dead birds’ management, 43 % of the farmers bury them,30 % re-feed them to animals, 30 % sell to fish farmers while 14 % subject them to burning. To assess the effect of the poor waste management on Minna shallow aquifers, an assessment of water quality from 20 randomly selected shallow wells inside the poultry farms was carried out. Samples of water were collected from the shallow wells and were analyzed for physical, chemical and bacteriological parameters. Results showed that the water quality is very poor; highly contaminated with faecal matter. Faecal as high as 348.67 cfu/100ml, total coliform 673.8 cfu/100ml and faecal streptococci of 220cfu/100ml were detected in some water samples from the wells. Turbidity and total dissolved solids of 67.4 NTU and 219.3 mg/L respectively were also recorded. For chemical parameters, Nitrate concentration of 232.5 mg/L, phosphate of 29.9 mg/L, arsenic of 0.72mg/L and chromium of 3.21mg/L were also detected in water from the shallow wells. Only 15% of the water samples satisfy WHO guideline value of 0 cfu/100 ml in dry season but reduced to 5 % in the wet season. For total coliform 10% satisfy WHO guideline value in dry season but none of the well sampled was total coliform free in the wet season. About 25 % were free from faecal streptococci during the dry season, but only 5 % was free from these bacteria in the wet season. Statistics (p> 0.05) show significant difference between coliform values in the wet and dry seasons. Generally the wells are polluted with coliforms which may have probably migrated from poultry waste dumps into the wells. The difference in physical parameter values was also statistically (p>0.05) significant between seasons, 55 % of the water samples satisfy WHO 5 NTU turbidity value in the dry season but the value reduced to 30% in the wet season. Lower values were recorded for TDS and EC in the wet season than in the dry season. For chemical tests, 50 % of the water meet up with WHO 50 mg/L nitrate guideline in the dry season and reduced to 35 % in the wet season. Statistics (p>0.05) shows no significant difference in the phosphate values for wet and dry seasons. Evaluation of equations generated by Logistic Regression presented a safe manure dumps and shallow wells in Minna to guarantee potable water.Minna soil, based on findings from lysimetric study is porous and present very small attenuation capacity to poultry wastes contaminants. Phosphates concentration of 12.91mg/L and nitrates concentration of 148.29mg/L contained in poultry manure were able to leach down to 2.5 meters depth of the soil within three months and bacteriological parameters, faecal coliform concentration of 343.89 cfu/100ml and total coliform of 353.84 cfu/100ml were able to migrate down to 2.5 meters in the subsoil of Minna two months after introduction of poultry manure into the experimental set up. Heavy metals (As, Zn, Cr, Cu and Mn) however did not leach beyond 0.5 meters depth of the soil after six months. Simulation with Visual MODFLOW predicted a five-year reduction in phosphates and nitrates concentration in the aquifer if indiscriminate and over application of poultry manure to Minna soil is checked, though the rate of heavy metal reduction is very small. For instance a reduction in concentration from 253.6 to 78 mg/L is recorded for nitrate,from 29.9 to 21.00 mg/L for phosphates, 0.74 to 0.60 mg/L for arsenic, zinc from 11.63.